2016
DOI: 10.1016/j.ijchp.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Model of the relationship between physical activity and quality of life

Abstract: Background/Objective: Literature shows that practicing physical activity improves the general health and quality of life of people with intellectual disabilities. However, there is little empirical research on the specific benefits physical activity provides and to what extent these benefits occur. The goal of this study was to examine the impact of perceptions of physical activity and the individualized support on each of eight quality of life-related domains and three higher-order quality of life factors. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 38 publications
4
27
0
5
Order By: Relevance
“…Such evidence is supported by the micro theory of Basic Psychological Needs (Deci and Ryan, 2012), which states that social environments conducted by significant persons (such as teachers, coaches, parents) favor the satisfaction of athletes’ basic needs for providing them with psychological experiences that positively affect their motivation and performance (Balaguer et al, 2012; Deci et al, 2013; González et al, 2015). In contrast, poorly adapted environments can frustrate the need of youngsters and consequently lower their participation in sports and sense of personal fulfilment, in addition to generate both emotional and physical fatigue (Bartholomew et al, 2011; Gurrola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such evidence is supported by the micro theory of Basic Psychological Needs (Deci and Ryan, 2012), which states that social environments conducted by significant persons (such as teachers, coaches, parents) favor the satisfaction of athletes’ basic needs for providing them with psychological experiences that positively affect their motivation and performance (Balaguer et al, 2012; Deci et al, 2013; González et al, 2015). In contrast, poorly adapted environments can frustrate the need of youngsters and consequently lower their participation in sports and sense of personal fulfilment, in addition to generate both emotional and physical fatigue (Bartholomew et al, 2011; Gurrola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the present trial we will also evaluate qualitative parameters such as QoL and cognitive and emotional aspects of participants with ID. We consider that QoL in seniors with ID is a very important parameter, which is influenced by PA and sports practice [86,87]. Beside the positive effects on QoL, PA may also improve cognitive and emotional aspects in people with ID, as previous studies have shown after implementing dance programs [64,88].…”
Section: Discussionmentioning
confidence: 96%
“…We look forward to having larger samples for testing and retesting, which would allow for greater consistency in similar studies in the future. Furthermore, we did not examine the influence of the family's socioeconomic status, physical activity and cross culture data (Carbó-Carreté, Guàrdia-Olmos, Giné, & Schalock, 2016); all such factors may affect fifth and sixth graders’ QoL. Hence, we recommend that future studies on the ESQoL scale consider these additional variables.…”
Section: Discussionmentioning
confidence: 98%